ANALISIS KETERKAITAN TINGKAT PENDIDIKAN PEREMPUAN DALAM TRADISI SINAMOT BATAK TOBA DI KECAMATAN SIDIKALANG KABUPATEN DAIRI - Novita Lastaruli Sinaga, Sudirman, (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2025)
This research aims to analyze the relationship between women's education levels in the sinamot Batak Toba tradition in Environment IX, Jalan Batukapur, Sidikalang Village, Dairi Regency. This research uses qualitative methods. The subjects in this study were 3 people consisting of 1 traditional figure (raja parhata) and 2 parents who had children at different levels of education. Data collection uses interview, observation and documentation techniques. The research results show that there is a relationship between the level of women's education and the sinamot values received in the sinamot tradition. Women's education is seen as a form of family investment that reflects values such as insight, responsibility and mental readiness to build a household. This affects expectations regarding the number of cinamot received. The higher a woman's education level, the greater the family's expectations of the value of the sinamot.